Current clinical practice in postoperative endovascular aneurysm repair imaging surveillance - Uthoff, Heiko; Geisbüsch, Philipp (Journal of vascular and interventional radiology, 2012)
Purpose: To investigate the current clinical practice in postoperative endovascular aneurysm repair (EVAR) imaging surveillance. Materials and Methods: Corresponding authors of EVAR publications during the years 2006-2011 and subscribers to an endovascular journal were invited to complete a 27-question online survey related to institutional demographics, standard post-EVAR imaging surveillance, and imaging protocols in special circumstances (eg, renal insufficiency). Results: The survey was completed by 515 of 9,631 physicians performing EVAR from 52 countries. Of respondents, 65.3% were affiliated with experienced centers where EVAR has been performed for > 10 years or with > 50 EVAR procedures performed per year. Computed tomography (CT) angiography was the modality used most often for standard surveillance with a maximum time interval between studies of 12 months in 78.8% of centers out to 5 years. Experienced centers were more likely to delay follow-up imaging to 1 year after an unremarkable initial post-EVAR imaging study (P < .001), to extend surveillance intervals > 12 months (P = .043), and to use ultrasound (P < .01) for surveillance. After the detection of a type II endoleak, CT angiography was favored for follow-up by 59.4% of the respondents. Experienced centers were more likely to favor ultrasound (P = .006) and to schedule this follow-up examination later (after 6-12 months, P < .001). Of respondents, 62.8% used a glomerular filtration rate threshold of < 30 mL/min for not performing contrast-enhanced CT scan. In patients with renal insufficiency, most respondents performed ultrasound with or without a concomitant noncontrast CT scan. Conclusions: CT is the most frequently used method of long-term surveillance after EVAR. Use of ultrasound for long-term surveillance, extension of follow-up time intervals, or both were most often reported in experienced centers.